Peningkatan Kualitas Hidup Pekerja Non Formal Pada Masyarakat Desa Sei Bamban Kecamatan Sei Bamban Kabupaten Serdang Bedagai - Hasanuddin Hasanuddin; Rana Fathinah Ananda (Universitas Medan Area, 2022)
Informal sector workers are people who work without work relations, meaning that there is no agreement that regulates the elements of work and power. In this case, the informal workers feel pressured because the scope of their work is limited which results in a decrease in their income during this pandemic, causing stress. Therefore, it is necessary to improve the quality of working life in the community, especially in Sei Bamban Village. One way to deal with stress is to cultivate peace of mind by considering the pandemic as a process that will make us grow and be much stronger than before. The purpose of this community service activity is to minimize stress on the community so as to be able to maintain the mental welfare of the community during this pandemic. In addition, this activity also aims to provide and strengthen the community as a means to develop themselves and have the ability to cope with stress so that they can achieve a quality work life. The results of this service are expected to help provide peace of mind for the community so that it becomes a good practice, is liked by the community and has the opportunity to be disseminated more widely. Thus the quality of the population in responding to problems during this pandemic can be maintained properly.